Ficcionalidade religiosa e o grotesco em A Montanha Sagrada, de Alejandro Jodorowsky - Santos Neto, Romeu Villa Flor (2023)
Although battered by indistinct use, the expression that “art imitates life” presupposes, if we admit it to be valid, that we are faced with language appropriations that are not always obvious. Of these, we can see those where the language of a religious nature sometimes crosses the boundaries of an apparently solemn or credible expression, typical of what common sense attributes as characteristic of religious tradition, to settle in the realms of the unusual, a realm recurrently shared by artistic creation. Among the multifaceted expressions of this imaginary, it is from the category of grotesque that the present work investigates the religious fictionality in cinema, using The Holy Mountain, a feature film by Chilean filmmaker Alejandro Jodorowsky, as a cutout. It makes a mediation between religion and art based on the theory developed by Russian philosopher Mikhail Bakhtin (1895-1975) about the work of French writer François Rabelais (1494-1553), aligning a transposition of Bakhtinian literary criticism to the cinematographic criticism of The Holy Mountain, having as a common thread the symbolic repertoire in both.